Lateral moraine elevation differences along a debris covered moraine - van Woerkom, Teun; Kraaijenbrink, Philip (Zenodo, 2019)
Debris-covered glaciers in the Himalaya play an important role in the high-altitude water cycle. The thickness of the debris layer is a key control of the melt rate of those glaciers, yet little is known about the relative importance of the three potential sources of debris supply: the rockwalls, the glacier bed and the lateral moraines. In this study, we hypothesize that mass movement from the lateral moraines is a significant debris supply to debris-covered glaciers, in particular when the glacier is disconnected from the rockwall due to downwasting. To test this hypothesis, eight high-resolution and highly accurate digital elevation models from the lateral moraines of the debris-covered Lirung Glacier in Nepal are used. These are created using structure from motion (SfM), based on images captured using an unmanned aerial vehicle between May 2013 and April 2018. The analysis shows that mass transport results in an elevation change on the lateral moraines with an average rate of -0.31 +/- 0.26 m/year during this period, partly related to sub-moraine ice melt. There is a higher elevation change rate observed in the monsoon (-0.39 +/- 0.74 m/year) than in the dry season (-0.23 +/- 0.68 m/year). The lower debris aprons of the lateral moraines decrease in elevation at a faster rate during both seasons, probably due to the melt of ice below. The surface lowering rates of the upper gullied moraine, with no ice core below, translate into an annual increase in debris thickness of 0.08 m/year along a narrow margin of the glacier surface, with an observed absolute thickness of approximately 1 m, reducing melt rates of underlying glacier ice. Further research should focus on how large this negative feedback is in controlling melt and how debris is redistributed on the glacier surface. This dataset contains the elevation differences on the moraine as presented in the van Woerkom et al. (2019). : Further funding was provided by the Nederlandse Organisatie voor Wetenschappelijk Onderzoek (grant no. 016.161.308).